Increasing Employee Engagement Through Management Of Job Demands And Supervisor Support Educational Institutions - Suhardoyo; Sinta Rukiastiandari; Isyana Emita (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
There are many companies or organizations that have’n been able to create a balance of job demands and supervisory support as a variable for employee work engagement, causing many physical and psychological health problems that affect performance and affect productivity with a decrease in quality. the resulting product, the burden of product repair costs increases, increased employee absenteeism and low employee engagement which results in decreased employee productivity. We conducted this research with the aim how much influence job demands and supervisor support variables on employee engagement variables. By using a cross-sectional study research method, with a probability sampling of 92 employees of the Educational Institutions from a difference of 167 employees. Analysis of research data using Multiple Linear Regression Analysis with the SPSS program. 23. Based on research and after processing the data, it shows that job demands have a negative relationship of 0.326 with employee work engagement, while supervisor support has a positive relationship of 0.431. While job demands and supervisor support together have a significant effect on employee job engagement. 71.44%, while the remaining 28.56% is explained by other variables not included in this study.